Peningkatan Hasil Belajar Matematika Siswa pada Materi Pola Bilangan Menggunakan Media Kartu Bilangan di Sekolah Menengah Pertama - Ancelina Dosantos Saldaha; Jakobus Nifanngelyau; Karten Halirat (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This study aims to analyze the effectiveness of using number card media in improving students’ learning outcomes on number pattern material. The research method employed was an experimental approach with a one-group pretest-posttest design involving 23 students as research subjects. The research instrument was a learning outcome test that had been validated through expert judgment and tested for reliability using Cronbach’s Alpha, which obtained a value of 0.682 categorized as moderate. Data were analyzed descriptively and inferentially using normality and homogeneity tests, paired sample t-test, and N-Gain calculation. The results showed a significant improvement between the pretest scores (mean = 22.78) and posttest scores (mean = 84.30), with the paired sample t-test indicating a sig. (2-tailed) value smaller than the significance level (0.000 ≤ 0.05), suggesting a significant difference. The average classical N-Gain of 0.79 was categorized as high, with 74% of students achieving improvement in the high category and 26% in the moderate category. These findings demonstrate that number card media plays a significant role in facilitating students to construct an understanding of abstract concepts through concrete learning experiences, in line with Piaget’s and Bruner’s constructivist theory.